Effect of predessors, soil cultivation and fertilization on the harvest and the quality of cereal grains of corn in the conditions of Luhansk region - Маслійов, С. В.; Мацай, Н. Ю.; Циганкова, Н. А.; Сахно, М. А. (Scientific Progress & Innovations, 2018)
The harvest of most field crops, including corn, depends on those conditions which are pre-crops in the rotation. The location of the corn after a good predecessors not only increases the yield, but also improves soil fertility. It has been established that fertilizers and soil cultivation help to increase the yield of corn. In the conditions of deficit and high cost of mineral fertilizers, the issue of their replacement by organic, which helps to improve the ecological and phytosanitary state of both soil and corn, remains weak, providing quality and cheap grain products. In this regard, the determination of the value of winter wheat, barley, maize for grain and sugar beet, as the main predessors of maize, grown on different backgrounds of fertilizer and basic cultivation of soil, in increasing its yield is of a particular relevance. Experiments were conducted on experimental areas of Luhansk Taras Shevchenko National University in 2016–2018. Taking into account the importance of the problem, the authors pointed out the prospect on the basis of complex studies to determine the effect of stems and propagation predessors at different backgrounds of fertilization and soil cultivation on elements of its fertility, phyto-sanitary condition and productivity of corn crops in the conditions of agriculture biologization.